Impedance characteristics of power distribution grids in nanoscale integrated circuits. - Mezhiba, A.V (IEEE Transactions on VLSI systems)
The essential design characteristic of nanoscale integrated circuits is increased interconnect complexity. Conductors at different levels of the interconnect hierarchy have highly different physical and, consequently, electrical characteristics. These interconnect lines also exhibit inductive behavior due to enhanced switching speed of nanoscale devices, making interconnect design and analysis difficult. The design of robust and area efficient power distribution networks for high-speed integrated circuits has therefore become a challenging task. The impedance characteristics of multilayer power distribution grids and the relevant design implications are the subject of this paper. The power distribution network spans many layers of interconnect with disparate electrical properties. Unlike single-layer grids, the electrical characteristics of multilayer grids vary significantly with frequency. As the frequency increases, a large share of the current flow is transfered from the low-resistance upper layers to the low-inductance lower layers. The inductance of a multilayer grid therefore decreases with frequency, while the resistance increases with frequency. The lower layers of multilayer power grids provide a low-inductance current path, significantly reducing the grid impedance at high frequencies. Multilayer power distribution grids extend to the lower interconnect layers, exhibiting superior high-frequency impedance characteristics as compared to power distribution grids built exclusively within the upper, low-resistance metal layers. A significant share of metal resources to distribute the global power should therefore be allocated to the lower metal layers. An analytic model is also presented to determine the impedance characteristics of a multilayer grid from the inductive and resistive properties of the comprising individual grid layers.